2014
DOI: 10.1186/s12985-014-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of H3N2 influenza A viruses isolated from Ontario swine in 2011 and 2012

Abstract: BackgroundData about molecular diversity of commonly circulating type A influenza viruses in Ontario swine are scarce. Yet, this information is essential for surveillance of animal and public health, vaccine updates, and for understanding virus evolution and its large-scale spread.MethodsThe study population consisted of 21 swine herds with clinical problems due to respiratory disease. Nasal swabs from individual pigs were collected and tested by virus isolation in MDCK cells and by rtRT-PCR. All eight segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…1). Many of these variations are within known antigenic domains, e.g., antigenic sites A, B, C, D, and E (18,(25)(26)(27). Among these, 4 are in antigenic site A, whereas 10 are in antigenic site B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Many of these variations are within known antigenic domains, e.g., antigenic sites A, B, C, D, and E (18,(25)(26)(27). Among these, 4 are in antigenic site A, whereas 10 are in antigenic site B.…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of TRIG-H3N2 virus infections in U.S. swine were first reported in a few states in 1998 and have spread to many other states (11) and Canada (17,18). The current circulating swine H3N2 viruses in North America, together with A(H3N2)v viruses, were termed "lineage IV" based on the phylogenetic analysis with earlier swine H3N2 isolates (13,(17)(18)(19). The majority of A(H3N2)v isolates since 2011 have acquired the matrix gene from the 2009 pandemic H1N1 virus (2,20), which has enhanced the replication and transmission of A(H3N2)v viruses in swine (21,22), potentially increasing the risk of human infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of aa substitutions have been observed in previously identified antigenic sites and substitutions are presented in Figure 5 and Table S1. The most changes, were observed when 13 Canadian H3N2 viruses were compared with an Ontario virus from 2011, (A/SW/ON/103-18/11/H3N2) [15]. The number of aa changes relative to the latter virus for each antigenic site is also displayed in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…In more recent studies, the A(H1N1)pdm09 has been identified as the most prevalent H1N1 virus in Ontario swine [12], and H1N2 reassortants have been documented [12,13]. Different types of novel H3N2 reassortants have been documented in several different studies [14,15], as well as ongoing circulation of the trH3N2 virus [15,16]. …”
Section: Introductionmentioning
confidence: 99%